Modelling and analysis of the influences of various liquid sloshing characteristics on tank truck dynamics. (30th July 2019) - Wan, Ying; Zhao, Weiqiang; Zong, Changfu; Zheng, Hongyu; Li, Zhenyang
This paper focuses on the degree of vehicle-liquid coupling and its influence on the whole vehicle in actual manoeuvres and the modelling theory of liquid sloshing in liquid tank trucks. A complicated two-way coupled dynamic model and three simplified models for tank trucks were developed. On the basis of the four models, the vehicle-liquid coupling dynamic characteristics and their influence on the whole vehicle are discussed from the aspects of lateral handling stability and longitudinal braking performance, with various actual manoeuvres of different emergency levels.